SLAB SURFACE TEMPERATURE IN SUBDUCTION ZONES: INFLUENCE OF THE INTERPLATE DECOUPLING DEPTH AND UPPER PLATE THINNING PROCESSES - Arcay D.; Tric E.; Doin M.-P. (My University, 2007)
The thermal state of the top of the subducting plate is strongly affected by the mantle wedge flow structure. We identify three main factors controlling the influence of the corner flow on the slab surface temperature: (1) the mantle rheology, (2) the interplate decoupling depth, and (3) the intensity of thermomechanical ablation of the overriding plate. The first two factors are discussed using results from published simulations. We perform 2D numerical simulations of mantle wedge flow to assess the role of the third factor. The non-Newtonian rheology depends on temperature, pressure, yield stress, and composition. The thermochemical convection code includes a water transfer model and the water weakening effect on mantle rocks. Slab dehydration triggers water saturation of the overlying mantle wedge and upper plate. When weakening of mantle rocks by hydration is included in the simulations, the interplate decoupling depth decreases and the upper plate thermal thinning increases. A relatively cold blanket develops on top of the slab below the interplate decoupling depth. Cold materials removed from the thinned upper plate are advected by the corner flow and are accreted to the viscous layer dragged along the slab surface. As a result, the thickness of the insulating layer covering the slab surface increases with the water weakening effect, together with the upper plate thermal thinning rate. Pressure-temperature (P-T) paths followed by crustal rocks during subduction quantify the influence of upper plate thinning processes on the slab surface thermal state. The slab surface temperature below 100 km can be lowered by as much as 130 °C due to increased thermal convection at the base of the upper plate. At shallower depths (< 100 km), this effect competes with the heating of the slab induced by a shallowing of the interplate decoupling depth. For a small water weakening effect, the enhanced corner flow mainly yields a shallow decoupling depth and warms the slab top from 50 to 100 km. For a large weakening effect, the slab surface is cooled by convective drips detaching from the overriding lithosphere that counter-balance the effect of a shallow decoupling depth. P-T paths in case of efficient upper plate thinning are thus inferred to be uniformly colder than predicted from the slab thermal parameter (age × velocity) and non-Newtonian wedge rheology. © 2007 Elsevier B.V. All rights reserved.
Keywords: MANTLE WEDGE; RHEOLOGY; SLAB THERMAL STATE; SUBDUCTION; WATER WEAKENING